2004
DOI: 10.1002/mus.20053
|View full text |Cite
|
Sign up to set email alerts
|

Technology literature review: Quantitative sensory testing

Abstract: The development of the personal computer has simplified the process of quantitating sensory thresholds using various testing algorithms. We reviewed the technical aspects and reproducibility of different methods to determine threshold for light touch-pressure, vibration, thermal, and pain stimuli. Clinical uses and limitations of quantitative sensory testing (QST) were also reviewed. QST is a reliable psychophysical test of large- and small-fiber sensory modalities. The results of QST are highly dependent on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
196
1
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(221 citation statements)
references
References 80 publications
5
196
1
12
Order By: Relevance
“…Indeed, an inverse relationship between age and intraepidermal nerve fibre density has been previously described [18,19]; the influence of sex, height, weight and BMI is less certain [18,20,21].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, an inverse relationship between age and intraepidermal nerve fibre density has been previously described [18,19]; the influence of sex, height, weight and BMI is less certain [18,20,21].…”
Section: Discussionmentioning
confidence: 97%
“…The objectivity of the method of measuring sensitivity has been questioned by Freeman et al, who proposed that subjects can deceive the examiner [44]. On the other hand, Chong and Cros concluded that the reliability is highly dependent on accurate use of methodology [23]. In the current study, the first and last measurement of each trial was made at the same frequency (32 Hz) to test the accuracy.…”
Section: Discussionmentioning
confidence: 76%
“…To evaluate sensibility, quantitative sensory testing (QST) has frequently been used in different clinical, epidemiologic, and research studies [23]. There are various QST methods, such as a simple patient answer of yes or no whether stimuli could be identified [24], choice between one out of two time periods that include stimuli [25], or when the patient is asked to press a button when a vibration stimuli is perceived and to press again when the stimulus disappears (the method of limits) [26].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, more than 15 different methodological approaches to QST have been developed 207,211,212 , thereby limiting the possibility of a standardized assessment. The International Association for the Study of Pain has provided consensus criteria on use and interpretation of QST findings 213 , emphasizing that a standardized protocol, adequate equipment, trained personnel and use of standard reference values should be developed.…”
Section: Box 1 | Quantitative Sensory Testingmentioning
confidence: 99%